Smart Trash with Web Integrated Volume Monitoring and Sorting System via MQTT Protocol - Maya Rahayu; Muhammad Nurkholis Widlan; Ashari; Hutama Arif Bramantyo (E-JOINT (Electronica and Electrical Journal Of Innovation Technology), 2022)
The increasing human population makes each year its production increase significantly. People's ignorance to separate the types of waste has triggered various disasters. Many studies have aimed at tackling this problem, such as smart trash bins that can sort various types of organic and inorganic materials and detect waste. However, it can products with many functions are not all integrated into one product. Purpose of this research is to provide a product that can integrate various smart trash bin functions with a volume monitoring system and sorting metal, non-metal, and organic waste types monitored via the web using the MQTT Protocol. This research prototype consists of several devices, namely smart trash bin equipped with proximity sensors, capacitive proximity sensors, and infrared sensors. In addition, this system is equipped with an ultrasonic sensor to detect the height of the trash. The Wi-Fi module integrated this system with web applications and the MQTT protocol. Based on the test, the system has been running well since the sensor data collection test is 70%, the delay test from the sensor input to the actuator is 3.48 s, the ultrasonic sensor reading accuracy is 97.16%, and the throughput on the monitoring website is 5084.75 bytes/sec.